One-dimensional analysis of the convergent-divergent motive nozzle for the two-phase ejector: Effect of the operating and design parameters - Atmaca, Ayşe Uğurcan; Erek, Aytunç; Ekren, Orhan (Applied thermal engineering, 2020)
•A simplified 1-D model of the motive nozzle is built with HEM approach.•Comparisons are useful for the future nozzle design of R1234yf and R1234ze(E).•Nozzle outlet pressure is affected mainly by the outlet diameter and mass flow rate.•Parameters affecting the outlet pressure have influence on the nozzle efficiency.•R134a and R1234yf have similar throat diameters when compared to R1234ze(E). Two-phase ejectors are used in the refrigeration cycles to decrease the throttling losses and improve the performance. The subject of this paper is the motive nozzle which is the critical component of the ejector since the pressure distribution throughout the motive nozzle affects the secondary fluid to be entrained into the ejector. A simplified version of the one of the previously established one-dimensional (1-D) converging-diverging motive nozzle models is developed in this paper to calculate the pressure, temperature, velocity, and Mach number distributions. 1-D model of the nozzle is established based on the conservation equations of mass, momentum, and energy and the equation of state under steady, frictional, and adiabatic flow assumptions with the homogeneous equilibrium condition. Maximum differences of the pressure drop throughout the nozzle between the literature data and the calculated results are around 6% and 8% for CO2 and R134a nozzles, respectively. The main objective is investigating the effects of the subcooling temperature difference, inlet pressure (condenser temperature or pressure), mass flow rate, and motive nozzle outlet diameter for R134a, R1234yf, and R1234ze(E). Parametric comparisons and evaluations are used to lead the motive nozzle designs for the further numerical and experimental studies including these new generation refrigerants for R134a replacement.